(untitled) (Revista Espacio Regional, 2020)
The following study aims on analyzing briefly the relationship between the implementation of sanitary policies and the economic strengthen in the context of the emergence of capitalism. Through a historical view of the social health, it is briefly problematized, the sanitary social security of the population as a strategic tactical condition to move towards progress and industrialization. Considering the state need to empower the population growth, the maintenance of the productive power and its vitality, materialized in the human capital, the main conclusions allow to understand the close link between the public health and the care of private interests, unveiling diffuse borders between what is considered public associated with the State and the private needs related to the market.